Impact of multifocal or multicentric disease on surgery and locoregional, distant and overall survival of 6,134 breast cancer patients treated with neoadjuvant chemotherapy - Ataseven, Beyhan; Lederer, Bianca; Blohmer, Jens-Uwe; Denkert, Carsten; Gerber, Bernd; Heil, Jörg; Kühn, Thorsten; Kümmel, Sherko; Rezai, Mahdi; Loibl, Sibylle; Minckwitz, Gunter von (Annals of surgical oncology, 2015)
The impact of tumor focality on type of surgery, local recurrence rate, and survival after neoadjuvant chemotherapy (NACT) for breast cancer is not fully understood. This study aimed to compare local recurrence-free survival (LRFS), disease-free survival (DFS), and overall survival (OS) according to focality stratified by type of surgery and pathologic complete response (pCR), with a focus on breast conservation.
Published: 09 October 2014
Gesehen am 28.07.2020